Failure and potential of profit-loss sharing contracts: a perspective of New Institutional, Economic (NIE) theory - Aisyah Abdul-Rahman; Radziah Abdul Latif; Ruhaini Muda; Mohamad Azmi Abdullah (Elsevier, 2014)
This paper theoretically evaluates why profit–loss sharing (PLS) contracts in Islamic banking fails and its potential for improvement within the scope of the New Institutional Economic Theory (NIE). The objective of the evaluation is to draw conclusive theoretical arguments of whether Islamic banking institutions in Malaysia should act as either financial intermediaries or entrepreneurs. Further, we analyze this issue from the perspective of agency theory, financial intermediation theory and entrepreneurship theory with four economic agents in the Islamic banking sector, namely entrepreneurs, depositors, shareholders, and the Islamic banks. Specifically, the first three economic agents represent the asset (equity-based financing), liability, and equity of the Islamic banks, respectively; while the latter is the Islamic banks, which act as a separate legal entity. Finally, we suggest that PLS contracts would best be positioned if Islamic banks play the role of genuine entrepreneurs.